The relationship between nutritional status and anemia in children aged 36-59 months with developmental problems - Marantika, Hasilia; Risnawati, Risnawati; Meihartati, Tuti; Sulistyoroni, Chandra (Science Midwifery, 2024)
The first five years are a very important period for the growth and development of children. Nutritional status and anemia are factors that influence child development. Based on an initial study conducted at PKM Long Ayan, DDTK screening (Early Detection of Growth and Development) in children aged 6 to 72 months as many as 323 children found the highest developmental problems in the age group 36-59 months with a total of 44 children (13.6%). To know the relationship between nutritional status and anemia in children aged 36-59 months with developmental problems in the Long Ayan Sub-Community Health Center Working Area. Quantitative associative with a cross sectional approach. The number of samples was 40 people with total sampling. Bivariate analysis with spearman rank Based on the results of the spearman rank correlation test, the p value is 0.011, where this figure <0.05 which means Ha is accepted and Ho is rejected, so it can be concluded that there is a relationship between nutritional status and child development problems, and for the anemia variable, based on the results of the spearman rank correlation test, the p value is 0.042, where this figure <0.05 which means Ha is accepted, so it can be concluded that there is a relationship between anemia status and child development problems. There is a relationship between nutritional status and anemia with developmental problems in children aged 36-59 months in the Long Ayan Pustu work area.